Produtividade e qualidade de grãos de arroz destinado à culinária japonesa em função do manejo da adubação nitrogenada em várzea de Roraima - Pereira, Maysa Mathias Alves (2015)
In the absence of specific recommendation of nitrogen fertilization and application management for BRS 358, as well as the influence of harvesting and storage time on the physical and physiological characteristics. The objective was to determine the dose and nitrogen application management in coverage for BRS 358, conducted in lowland Roraima that will provide greater agronomic and economic efficiency. The experiment was conducted in Roraima lowland area with continuous irrigation system in the municipality of Cornwall, from December 2014 to March 2015, in Gleysol Hápico tb dystrophic. The experimental design was a randomized block in split plot design (4x4), with four repetitions, totaling 64 sample units. The factor doses was allocated in the plots (50 kg ha-1, 100 kg ha-1, 150 kg ha-1, 300 kg ha-1) and the second factor managements of nitrogen application in the subplots: M1: 50% on base and 50% at 45 days after emergence (DAE); M2: 100% application at 15 DAE; M3: 25% at the base and 75% in coverage divided into ½ to 15 ½ and 45 DAE; M4: 25% base; 25% at 15 DAE; 25% at 35 DAE and 25% to 55 DAE. We evaluated the rice crop production components as the methodology recommended by the Standard Evaluation System For Rice. Due to harvest time and storage time (0 to 6 months) were evaluated the performance of integrated and polished whole grains (%), whiteness of grain and seed germination. The results show the influence of the nitrogen dose and application management on yield components evaluated, where the features were highly correlated, resulting in maximum productivity physical efficiency of 6.245 kg ha-1, maximum economic efficiency of 6.193 kg ha-1 with Application of 209 to 182 kg ha-1 of urea, respectively. The N, 50% at the base and 50% at 45 DAE, promoted greater increase in grain yield and paddy yield of whole grains, noting yield of whole whole grains at harvest above 65%, and when stored for six months at room temperature greater than 75%, regardless of the application management. To yield the best polished whole grain crop range was 38-45 DAF, with a yield of 50% and if the grain to be stored for six months, harvesting can be performed in 38-52 DAF, an increase of 30% in yield of whole grain harvesting done 52 DAF and 10% at 38-45 DAF. The percentage of germination was greater than 80% at harvest and reduced 50% when seeds were stored for six months. Application average of 200 kg ha-1 of N promotes better physical and physiological characteristics Additionally, increasing doses of N positive influence on the whiteness of the grain content.